A Distributed Blockchain Framework for Secure Healthcare Across Multiple Channels - Hadi, Hend Abdul Ameer; Ghani, Rana Fareed (Iraqi Journal of Science, 2025)
Communication and information technologies have facilitated the rapid adoption of electronic medical records, leading to patient privacy and data security concerns. Blockchain technology offers a promising solution to address these issues. However, scalability remains a significant challenge for blockchain-based electronic health records (EHR) systems. In this study, we aimed to develop and evaluate an EHR management system based on blockchain technology. Therefore, we propose a management model based on organizations and user roles and implemented it using Hyperledger Fabric and the InterPlanetary File System (IPFS). The blockchain consists of three channels: one for patient registration and EHR retrieval and two additional channels dedicated to two hospitals for storing patients’ EHRs. A scalable multichain e-health system using the Hyperledger Fabric platform provides a practical option to address scalability issues and protect patients’ privacy, security, and medical data. The proposed model uses IPFS to store medical images and generate hash values, which are then stored in the blockchain. The system was evaluated using Hyperledger Explorer and Hyperledger Caliper, focusing on several performance metrics: transactions per hour, transactions per minute, blocks per hour, blocks per minute, response time, maximum latency, minimum latency, average latency, throughput, CPU and memory usage, and runtime. A comparative analysis was conducted against single-ledger EHR systems to assess the proposed system’s performance. The Hyperledger Caliper report shows that the average latency for each organization ranges from 0.11 to 0.55, and the throughput ranges from 24.2 to 200 for 1000 assets at sending rates of 25, 50, 100, and 200.